UNDANG-UNDANG CIPTA KERJA DI TENGAH HIMPITAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020 - Irawan, Atang (LITIGASI, 2022)
The Job Creation Act is believed to be able to end the obesity of statutory regulations in Indonesia which often creates disharmony between laws and regulations which results in sectoral ego and bureaucracy in providing government services to the people, both in the form of permit and non-permit. The spirit of the Job Creation Act in the context of regulatory simplification is expected to accelerate national economic recovery in the midst of a pandemic and to cut bureaucracy in services for investment and MSMEs. However, along the way, the Constitutional Court Decision No. 91/PUU-XVIII/2020 has stated that Law No. 11 of 2020 concerning Job Creation does not have conditionally binding legal force as long as it is not interpreted as "no amendment are made within 2 (two) years, even if it cannot be resolved, it becomes permanently unconstitutional and the amended and revoked law is declared to be reinstated. This research is a normative legal research or literature research (doctrinal research), which uses primary and secondary legal materials. These two materials are used in order to obtain a comprehensive analysis and perspective on the legal issues discussed. This research was conducted in order to analyze the job creation law after the Constitutional Court's decision. The Job Creation Act is still in effect but cannot be implemented, therefore the government as the initiator must immediately assign the Minister of Law and Human Rights to revise the Job Creation Law as soon as possible so that the process of procedure and its formation with Law No. 12 of 2011, or amendment to Law No. 12 In 2011 by adding the omnibus method and the procedure for its formation. Keywords: Conditional unconstitutional.